The Role of Neurotransmitters in the Protection of Caenorhabditis Elegans for Salmonella Infection by Lactobacillus - Liu, Xiaozhen; Jiang, Leming; Li, Linyan; Yu, Hai; Nie, Shaoping; Xie, Mingyong; Gong, Joshua (Frontiers in Cellular and Infection Microbiology, 2020)
Salmonellosis is a common foodborne disease. We previously reported the protection of Caenorhabditis elegans from Salmonella Typhimurium DT104 infection by Lactobacillus zeae LB1. However, the mechanism is not fully understood. C. elegans exhibits behavior plasticity when presented with diverse pathogenic or commensal bacteria. Whether it can exert approach avoidance to S. Typhimurium through altering its neurological activity remains to be determined. In the current study, both the wild type and mutants defective in serotonin or dopamine production of C. elegans were used to investigate olfactory preference of the nematode to L. zeae LB1, DT104, and Escherichia coli OP50 by choice assays, and its resistance to DT104 infection and the protection offered by L. zeae LB1 using a life-span assay. The expression of target genes in C. elegans was also examined by real-time quantitative PCR. Results showed that pre-exposure to L. zeae LB1 did not elicit aversive olfactory behavior of the nematode toward DT104. Both mutants tph-1 and cat-2 succumbed faster than the wild type when infected with DT104. While pre-exposure to L. zeae LB1 significantly increased the survival of both the wild type and mutant tph-1, it provided no protection to mutant cat-2. Supplementation of dopamine resulted in both the resistance of mutant cat-2 to S. Typhimurium infection and the protection from L. zeae LB1 to the same mutant. Gene expression data also supported the observations in the life-span assay. These results suggest that both serotonin and dopamine play a positive role in the host defense of C. elegans to S. Typhimurium infection and that the L. zeae LB1 protection is not dependent on modifying olfactory preference of the nematode but mediated by dopamine that may have involved the regulation of p38-mitogen-activated protein kinase and insulin/insulin-like growth factor signaling pathways.